A phenomenology of direct observation in residency: Is Miller's 'does' level observable?. Issue 3 (23rd December 2022) - Rietmeijer, Chris B. T.; van Esch, Suzanne C. M.; Blankenstein, Annette H.; van der Horst, Henriëtte E.; Veen, Mario; Scheele, Fedde; Teunissen, Pim W.
Abstract: Introduction: Guidelines on direct observation (DO) present DO as an assessment of Miller's 'does' level, that is, the learner's ability to function independently in clinical situations. The literature, however, indicates that residents may behave 'inauthentically' when observed. To minimise this 'observer effect', learners are encouraged to 'do what they would normally do' so that they can receive feedback on their actual work behaviour. Recent phenomenological research on patients' experiences with DO challenges this approach; patients needed—and caused—some participation of the observing supervisor. Although guidelines advise supervisors to minimise their presence, we are poorly informed on how some deliberate supervisor participation affects residents' experience in DO situations. Therefore, we investigated what residents essentially experienced in DO situations. Methods: We performed an interpretive phenomenological interview study, including six general practice (GP) residents. We collected and analysed our data, using the four phenomenological lenses of lived body, lived space, lived time and lived relationship. We grouped our open codes by interpreting what they revealed about common structures of residents' pre‐reflective experiences. Results: Residents experienced the observing supervisor not just as an observer or assessor. They also experienced them as both a senior colleague and as the patient's familiar GP, which led to many additional interactions. When residents tried to act as if the supervisor was not there, they could feel insecure and handicapped because the supervisor was there, changing the situation. Discussion: Our results indicate that the 'observer effect' is much more material than was previously understood. Consequently, observing residents' 'authentic' behaviour at Miller's 'does' level, as if the supervisor was not there, seems impossible and a misleading concept: misleading, because it may frustrate residents and cause supervisors to neglect patients' and residents' needs in DO situations. We suggest that one‐way DO is better replaced by bi‐directional DO in working‐and‐learning‐together sessions. Abstract : Investigating direct observation in residency, Rietmeijer et al. report that the observer effect is much more material than previously understood, causing concern about the capacity to ever truly witness Miller's 'does' level of performance.